The Role of Motivation in Mediating the Influence of Career Development on Employee Performance - Fauziyana, Evi; Wijayanti Wardoyo, Dewie Tri; Witjaksono, Andre Dwijanto (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
This study was designed to determine the factors that affect employees' performance. The problem is the role of motivation in mediating the effect of career development on employee performance at Â PT. PLN (Persero) UP3 Bojonegoro Area. Research on motivation in mediating the effect of career development on employee performance at PT. PLN (Persero) UP3 Bojonegoro. The research uses quantitative methods; the population is employees at PT. PLN (Persero) UP3 Bojonegoro area as many as 135 people. The research sample was determined by accidental sampling and calculated using the Slovin formula, a sample of 57 people. The data analysis used in this research is PLS (Partial Least Square) analysis. The result is that career development has a positive effect on employee performance, career development positively affects motivation, and motivation has a positive effect on employee performance.